Design Of LPG Leak Detection Using Sensor TGS2610 Equipped SMS -Based Microcontroller ATmega328 - Paramarta, Pande Made Nova; Agung, IGAP Raka; Rahardjo, Pratolo (Majalah Ilmiah Teknologi Elektro; Vol 15 No 1 (2016): (January - June) Majalah Ilmiah Teknologi Elektro, 2016)
The disaster that occurred in communities one of which was a house fire caused by leakage of LPG which preceded the occupants leave the house. In anticipation of these events, LPG leak detection system remotely using SMS on a mobile phone handy so that residents know the situation / condition of LPG when leaving the house. when sensors  TGS 2610 detect that the LPG in case of leak, then the residents will receive SMS 'Gas Bocor'. When in a safe condition, residents no longer receive SMS. When sending SMS residents 'cek' to the GSM module, the GSM module sending SMS 'aman' to residents.   DOI:  10.24843/MITE.1501.08
Keywords: ATmega328, TGS2610, GSM module, LPG leakage.